Role of Manganese Forms on Black Gram (Vigna mungo) Seedling Growth: Effects of Mn Toxicity on Seeding of Vigna mungo - Khan, Zahid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2021)
The impact of concentration of manganese (Mn2+) forms on early seedling growth and some physiological attributes of black gram (Vigna mungo L.) have been reported in the current study. An adequate amount of 22.32 μg/mL (as in control solution) of Mn2+ was found to be crucial for proper growth and it also greatly impacts the process of photosynthesis and the amount of chlorophyll in the growing seedling. Reduced growth was observed as the concentration of Mn2+ was increased from 50 ppm up to 250 ppm. Reduced growth is due to various non-enzymatic coping mechanisms invoked by the plant to ease the metal stress which has several side effects on key plant growth attributes. One such defense strategy to reduce metal overload is the production of proline that can dilute the excess metal content. Chlorophyll content with respect to the age of the seedling is also studied and it brought interesting results.